Imaging Modalities Used for Frameless and Fiducial-Less Deep Brain Stimulation: A Single Centre Exploratory Study among Parkinson's Disease Cases - Krahulik, David; Blazek, Filip; Nevrly, Martin; Otruba, Pavel; Hrabalek, Lumir; Kanovsky, Petr; Valosek, Jan (Diagnostics (Basel, Switzerland), 2022)
Deep brain stimulation (DBS) is a beneficial procedure for treating idiopathic Parkinson's disease (PD), essential tremor, and dystonia. The authors describe their set of imaging modalities used for a frameless and fiducial-less method of DBS. CT and MRI scans are obtained preoperatively, and STN parcellation is done based on diffusion tractography. During the surgery, an intraoperative cone-beam computed tomography scan is obtained and merged with the preoperatively-acquired images to place electrodes using a frameless and fiducial-less system. Accuracy is evaluated prospectively. The described sequence of imaging methods shows excellent accuracy compared to the frame-based techniques.
Keywords: O-arm; Parkinson’s disease; deep brain stimulation; Nexframe